Navigating Public Relations Ethics in Educational Communication: A Qualitative Case Study of Information Services - Hidayatul Fadliah; Siti Hamidah; Robby Hidayat; Aprizon Dika Putra; Riska Meisyi Putri; Mardalena Mardalena; Anggia Pratiwi (Universitas Nurul Jadid Probolinggo, Indonesia, 2026)
This study aims to analyze the implementation of public relations ethics in managing information services and institutional communication within an educational institution using Talcott Parsons’ AGIL functionalism paradigm as the analytical framework. The research employed a qualitative case study approach to obtain an in-depth understanding of ethical communication practices in a real-world educational context. Data were collected through direct observations, semi-structured interviews, and document analysis and were analyzed using an interactive model involving data condensation, data display, and conclusion drawing and verification. The credibility of the findings was ensured through source triangulation, technique triangulation, and crystallization. The findings reveal that public relations ethics are implemented through transparency, integrity, politeness, and accountability in information services, contributing to stronger stakeholder trust and more effective institutional communication. Nevertheless, the study also identifies challenges, including limited digital communication competence, insufficient collaboration with external stakeholders, and the absence of formal ethical guidelines for digital communication. These findings imply that educational institutions should develop comprehensive ethical communication frameworks to strengthen organizational integration, improve stakeholder engagement, and sustain public trust amid ongoing digital transformation.